KKN TEMATIK UNRAM 2022 MELAKSANAKAN PEMBUATAN PESTISIDA ALAMI BERBAHAN DAUN PEPAYA DI DESA KARANG BAYAN - Yuniarto , Kurniawan; Setiawan, Aldi Januar; Alfianita, Aulia; Ekaputri, Baiq Mayzahra Aulia; Miqraj, Gaosi Samdani; Sari, Gita Sagita; Labysta, Gyso Assykar; Pramesty, Kinkin Ayu; Wulandari, Ririn; Sudarmaji, Sudarmaji; Saputri, Yuni (Jurnal Wicara, 2023)
The agricultural sector is the backbone of the community's economic activities in general. Not only as a source of food for the people every day, but as a source of foreign exchange for the country as well. Karang Bayan Village, which is located in Lingsar District, West Lombok Regency, is an example of a village with a community that until now still relies on the agricultural sector as a life support. This can be seen from the livelihoods of the people, most of whom work as farmers. The commodities planted by Karang Bayan Village farmers are rice, mangosteen, rambutan and durian. The cultivation of these plants does not always run smoothly, one of the factors is the presence of Plant Pest Organisms (OPT). One way to control pests is to use pesticides on plants. Pesticides consist of 2 types, namely chemical pesticides and natural or vegetable pesticides. One example of a plant that can be used as a pesticide is the papaya plant (Carica papaya). Given that papaya leaves are very easy to find and are not put to good use by the Karang Bayan community, the purpose of this service activity is to provide training and assistance in making natural papaya pesticides in Berembeng Timur Hamlet, Karang Bayan Village, Lingsar District, West Lombok Regency. Pesticide manufacturing activities This natural pesticide program starts on December 27, 2022 until January 24, 2023. This natural pesticide production and training activity aims to provide information and invite the public to be able to make their own natural pesticides so that they can be used to reduce the number of pests such as fleas on cultivated plants, especially in mangosteen plant.